Bacterial contamination of surgical loupes and headlights. Issue 5 (22nd April 2019) - Purcell, C; Moolman, N; MacKay, C; Hatchette, T F; Trites, J; Taylor, S M; Rigby, M H; Hart, R D
Abstract: Background: Medical equipment can transmit pathogenic bacteria to patients. This single-institution point prevalence study aimed to characterise the types and relative amount of bacteria found on surgical loupes, headlights and their battery packs. Method: Surgical loupes, headlights and battery packs of 16 otolaryngology staff and residents were sampled, cultured and quantified. Plate scores were summed for each equipment type, and the total was divided by the number of users to generate mean bacterial burden scores. Residents completed a questionnaire regarding their equipment cleaning practices. Results: The contamination rates of loupes, headlights and battery packs were 68.75 per cent, 100 per cent and 75 per cent, respectively. Battery packs cultured more bacteria (1.58 per swab ± 1.00) than loupes (0.75 per swab ± 0.66; p = 0.024). Headlights had non-significantly greater growth (1.50 per swab ± 0.71) than loupes ( p = 0.052). Bacterial growth was significantly higher from inner surfaces of loupes ( p = 0.035) and headlights ( p = 0.037). Potentially pathogenic bacteria were cultured from the equipment of five participants, including: Pantoea agglomerans, Acinetobacter radioresistens, Staphylococcus aureus, Acinetobacter calcoaceticus baumannii complex and Moraxella osloensis . Conclusion: This study demonstrates that surgical loupes and headlights used in otolaryngology harbour non-pathogenic skin flora and potentially pathogenic bacteria.